LEGAL ANALYSIS OF THE APPLICATION OF REHABILITATION BASED PARTICULAR DETERRENCE IN THE CONCURRENT CRIMES BY CHILDREN - Diena Mawaddah (Universitas Negeri Semarang, 2026)
Handling concurrent criminal acts (concursus) by children still faces an inaccurate approach to punishment between the prevention and protection aspects of children's rights. The dominance of the retributive approach results in less than optimal efforts to reduce child recidivism sustainably. This study aims to analyze the concept, legal basis, and application of rehabilitation-based particular deterrence in judges' considerations in juvenile court decisions. This study uses a normative juridical method with analytical descriptive specifications. The approach used includes legislative, conceptual, and case approaches to juvenile court decisions. Primary legal materials include Law Number 11 of 2012 concerning the Juvenile Criminal Justice System, Law Number 35 of 2014 concerning Child Protection, concursus regulations in the Criminal Code, and Law Number 1 of 2023. The analysis was conducted qualitatively through normative interpretation and synchronization with judicial practice. The results of the study indicate that the application of rehabilitation-based particular deterrence plays a strategic role in handling concursus by emphasizing the development and change of children's behavior. This approach is capable of reducing the risk of recidivism while also embracing the principle of the best interests of the child. However, its implementation is inconsistent in judges' considerations, particularly regarding proportionality of punishment and the integration of rehabilitative aspects. Thus, the lack of synchronization between norms and practices has the potential to undermine the effectiveness of juvenile sentencing objectives.